Evaluation of new satellite-based approach procedures enabled by advanced receiver autonomous integrity monitoring algorithms: A case study of a Brazilian airport - Balvedi, Glaucia Costa; Fregnani, Jose Alexandre Tavares Guerreiro; Murça, Mayara Conde Rocha; Monico, Joao Francisco Galera [UNESP]; Saotome, Osamu (Institute of Electrical and Electronics Engineers (IEEE), 2023)
The advent of the Performance-Based Navigation (PBN) concept supported by Global Navigation Satellite Systems (GNSS) has brought significant changes in airspace design, resulting in more direct, flexible and precise routes worldwide. With the evolution of integrity monitoring algorithms, satellite navigation systems also have the potential to support approach operations with more stringent performance requirements, even in equatorial and low altitude regions impacted by ionospheric scintillation, providing several operational benefits. In particular, airports that currently lack the ground-based infrastructure required for instrument approaches can benefit from increased accessibility during adverse weather conditions. In this paper, we evaluate the potential implementation of new GNSS-based approach procedures - specifically, RNP 0.1 and LPV-250 - at Navegantes International Airport (SBNF) in Brazil based on the use of multi-constellation and multi-frequency signals enabled by the Advanced Receiver Autonomous Integrity Monitoring (ARAIM) algorithm. The availability provided by ARAIM was compared with the ones obtained with the currently used RAIM algorithm. For this, data from a GNSS receiver located at a similar geomagnetic latitude as SBNF is analyzed. The services availability arranged by day and hour demonstrate the best time window for operations considering ionospheric scintillation occurrences. These results are crossed with historical weather data to evaluate the additional SBNF accessibility provided by potential implementations of more stringent approach procedures with lower weather minima supported by ARAIM, in comparison with the RNP 0.2 approach procedures currently implemented at the airport. The resulting operational benefits are then quantified through the potential savings that could be achieved with the reduction of flight diversions due to adverse weather.
Keywords: Approach Procedures; Integrity Monitoring; Ionospheric Scintillation; Performance-Based Navigation; Satellite Navigation Systems